Preparation and Drug-Delivery Properties of Metal-Organic Framework HKUST-1 - P. Khadiv-Parsi; H. Moradi; M. Shafieeardestani; P. Taheri (Iranian Journal of Chemical Engineering)
In this research, the metal-organic framework of HKUST-1 (Hong Koung University of Science and Technology) was synthesized for use in modern drug delivery systems by the thermal solvent method. It was activated in two conditions: under vacuum pressure and by a freeze-drying method. The synthesized HKUST-1 Metal-Organic Framework was analyzed by IR, XRD, BET, and SEM. In order to examine and compare the results, the IR sample was synthesized using the sample before and after the activation of the sample. Regarding the XRD pattern, the peak area of 2θ = 11.760 showed the highest intensity. The SEM images showed an octagonal morphology in which the particle size was in the range of 5-65 μm. Furthermore, by using the BET method, the surface area of 1306 m2/g was calculated.